Um Senhor Tavares: ensaios e erros - Lilian Jacoto (Investigação, 2020)
Gonçalo M. Tavares is a writer who thrives on thought. His fiction feeds off a large epistemological debate that finds in Literature a privileged field of experience and observation of the ethical dilemmas in the posthuman world. As a sort of speculative anthropologist, he employs multiple genres to foster a wide debate on the limits of that which is human, its existential scope, its body and subjectivity. This book focuses on a procedure which Tavares himself claims to make use of, under the influence of Roland Barthes: the procedure of "writing the reading". It consists of trials and errors that sometimes endeavor to imitate the author's own gesture of writing as an attempt to "write along with" Gonçalo M. Tavares, and sometimes outline the presence of others with whom he shares this this gesture. The essays here comprised seek to measure the intensity of the enstrangement brought on by Tavares' writing as the cornerstone of a fiction whose telos is to lend some lucidity to the contemporary world while making it spin into absurdity.